Bayesowska aktualizacja rozkładu liczby odszkodowań w ubezpieczeniach komunikacyjnych - Szreder, Mirosław; Pobłocka, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
An increasing amount of information collected in various areas of economic and social activities makes the problem of processing information more and more important. Efficient decision making requires the use of proper rules for processing and updating information used by decision makers. The Bayesian approach is considered to be one of the most appealing ways for updating the present knowledge on the basis of newly collected data. The paper presents opportunities of the Bayesian approach in updating the distribution of the number of claims when new information becomes available. An empirical example discussed in the paper, which uses actual data obtained from a Polish insurance company, exhibits some opportunities of Bayesian tools in actuarial problems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 292-304